The Type Fragmentation Patterns Confirmed Acetaminophen By Using Liquid Chromatography-Mass Spectroscopy (LCMS) From Herbal Medicine (Jamu) - Muhammad Taupik; Endah Nurrohwinta Djuwarno; Moh Adam Mustapa; Wiwin R Kunusa; Jafar La Kilo; Muhamad Handoyo Sahumena (Faculty of Science and Technology Universitas Islam Negeri Ar-Raniry, 2021)
Abstract: The Jamu or herbal medicine were adulterated with chemical drugs in the last twenty years. One of the chemical drugs that are commonly added to herbal medicine is acetaminophen. Acetaminophen is generally considered an analgesic-antipyretic drug. The research aims to identify the content of paracetamol and its amount added to the jamu. This study consisted of 6 jamu or herbal medicine samples with different brands. The TLC method conducted the qualitative analysis using the mobile phase n-hexane: ethyl acetate (1:1). Three positive samples containing acetaminophen were obtained: D, E, and F. The three positive samples containing acetaminophen were calculated using the LCMS method. Quantitative analysis was conducted with LCMS using a reversed-phase with a mobile phase of acetonitrile: water (15%>: 85%> v/v) at a flow rate of 0.2 mL/min and an injection volume of 5 µL, it was obtained the levels of acetaminophen in sample D as much as 0.16 g/2 g of sample, in sample E of 0.63 g/7 g of sample, and sample F of 0.56 g/7 g of sample. Although the acetaminophen content in herbal medicine is relatively small, according to the Regulation of the Minister of Health of Indonesia No. 007 of 2012, traditional medicine or herbal medicine should not contain synthetic chemicals.Abstrak: Dalam dua puluh tahun terakhir, banyak jamu yang dipalsukan dengan obat-obatan kimia. Salah satu obat kimia yang biasa ditambahkan pada jamu adalah asetaminofen. Acetaminophen umumnya dianggap sebagai obat analgesik-antipiretik. Penelitian ini bertujuan untuk mengetahui kandungan parasetamol dan jumlah yang ditambahkan pada jamu. Sampel penelitian ini terdiri dari 6 sampel jamu dengan merek yang berbeda. Analisis kualitatif dilakukan dengan metode KLT menggunakan fase gerak n-heksana: etil asetat (1:1). Diperoleh tiga sampel positif mengandung asetaminofen, yaitu sampel D, E, dan F. Tiga sampel positif mengandung asetaminofen dihitung menggunakan metode LCMS. Analisis kuantitatif dilakukan dengan LCMS menggunakan fase terbalik dengan fase gerak asetonitril: air (15%>:85%> v/v) pada laju alir 0,2 mL/menit dan volume injeksi 5 µL. Diperoleh kadar asetaminofen pada sampel D sebanyak 0,16 g/2 g sampel, pada sampel E sebesar 0,63 g/7 g sampel, dan pada sampel F sebesar 0,56 g/7 g sampel. Meskipun kandungan asetaminofen dalam jamu relatif sedikit, namun menurut Peraturan Menteri Kesehatan RI No. 007 Tahun 2012, obat tradisional atau jamu tidak boleh mengandung bahan kimia sintetik.